Perbedaan dan Persamaan Metode Penemuan Hukum Islam dan Metode Penemuan Hukum Positif - Bakhtiar, Bakhtiar (Pagaruyuang Law Journal, 2018)
The aims of this paper is to describe the methods of Islamic law discovery and methods of finding positive laws and their similarities and differences. The type of research the author uses in this paper is the study of normative law (normative legal research) the data acquisition of library materials or secondary data. The data analysis techniques (legal materials) used is to use qualitative analysis. So to draw the conclusions of each data, whether in the form of principles, conceptions, or in the form of rules and legal norms, will be described analytically descriptively. From the results of research conducted, it can be understood that both Islamic law and positive law recognize that there is no rule of law or law is complete and in line with the present reality, there will always be shortcomings Consequences of such things, law enforcement such as judges and other legal officers should make legal discovery based on their respective sources of law, because only from the sources can be explored legal norms. In Islamic law, the invention of the law includes the method of literal interpretation (linguistic), kausasi (ta'lili) and synchronization. Whereas in positive law, include methods of interpretation, argumentation and the discovery of free law. Substantively, the two methods of legal discovery have differences and equations that allow to be compromised. This effort was made to look for new methods of legal discovery that are more responsive by exploring the legal values that live in society.